A fuzzy robust control scheme for vibration suppression of a nonlinear electromagnetic-actuated flexible system. (1st March 2017) - Tavakolpour-Saleh, A.R.; Haddad, M.A.
Abstract: In this paper, a novel robust vibration control scheme, namely, one degree-of-freedom fuzzy active force control (1DOF-FAFC) is applied to a nonlinear electromagnetic-actuated flexible plate system. First, the flexible plate with clamped-free-clamped-free (CFCF) boundary conditions is modeled and simulated. Then, the validity of the simulation platform is evaluated through experiment. A nonlinear electromagnetic actuator is developed and experimentally modeled through a parametric system identification scheme. Next, the obtained nonlinear model of the actuator is applied to the simulation platform and performance of the proposed control technique in suppressing unwanted vibrations is investigated via simulation. A fuzzy controller is applied to the robust 1DOF control scheme to tune the controller gain using acceleration feedback. Consequently, an intelligent self-tuning vibration control strategy based on an inexpensive acceleration sensor is proposed in the paper. Furthermore, it is demonstrated that the proposed acceleration-based control technique owns the benefits of the conventional velocity feedback controllers. Finally, an experimental rig is developed to investigate the effectiveness of the 1DOF-FAFC scheme. It is found that the first, second, and third resonant modes of the flexible system are attenuated up to 74%, 81%, and 90% respectively through which the effectiveness of the proposed control scheme is affirmed. Highlights: A novel acceleration-based fuzzy robust vibration control scheme was proposed. A nonlinear electromagnetic actuator was considered in this investigation. Simulation results revealed the effectiveness of the proposed control technique. Validity of the proposed control algorithm was demonstrated experimentally. Superiority of the proposed control scheme over pure acceleration feedback control was shown.